2001
DOI: 10.1099/0022-1317-50-5-421
|View full text |Cite
|
Sign up to set email alerts
|

Novel Helicobacter species isolated from rhesus monkeys with chronic idiopathic colitis

Abstract: Chronic, idiopathic diffuse colitis is a well recognised clinical and pathological entity in captive rhesus monkeys. Six rhesus monkeys were diagnosed with clinically debilitating, chronic diarrhoea. Histologically, colonic tissues were characterised as chronic, moderate to severe colitis and typhlitis, with diffuse mononuclear in¯ammation of lamina propria, reactive lymphoid hyperplasia and multifocal micro-abscesses. Colonic tissues were cultured for Salmonella spp. and Shigella spp.; all results were negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
54
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 15 publications
4
54
0
Order By: Relevance
“…However, this study did not perform colonic biopsies to ascertain if the H. cinaedi-positive monkeys had histological evidence of chronic colitis, a common finding in rhesus monkeys (Fernandez et al, 2002). Isolation of other novel helicobacters from inflamed colons of rhesus monkeys and cotton-top tamarins is also consistent with the increasing recognition of enteric helicobacters in children with gastroenteritis who reside in developing countries (Fox et al, 2001b;Lastovica & le Roux, 2000;Saunders et al, 1999) and the identity of enteric helicobacters in the lower bowel of children with inflammatory bowel disease (Thomson et al, 2011;Zhang et al, 2006). Our findings in this study are consistent with previous NHP studies, in that we identified Helicobacter jaachi sp.…”
Section: Discussionsupporting
confidence: 82%
“…However, this study did not perform colonic biopsies to ascertain if the H. cinaedi-positive monkeys had histological evidence of chronic colitis, a common finding in rhesus monkeys (Fernandez et al, 2002). Isolation of other novel helicobacters from inflamed colons of rhesus monkeys and cotton-top tamarins is also consistent with the increasing recognition of enteric helicobacters in children with gastroenteritis who reside in developing countries (Fox et al, 2001b;Lastovica & le Roux, 2000;Saunders et al, 1999) and the identity of enteric helicobacters in the lower bowel of children with inflammatory bowel disease (Thomson et al, 2011;Zhang et al, 2006). Our findings in this study are consistent with previous NHP studies, in that we identified Helicobacter jaachi sp.…”
Section: Discussionsupporting
confidence: 82%
“…Although H. cinaedi has been isolated from multiple organs and body fluids from both immunocompromised and immunocompetent patients, it has not been previously isolated from inflamed tissues of nonhuman primates (8). Interestingly, however, both H. cinaedi and H. fennelliae can cause diarrhea and bacteremia when inoculated into pigtail macaques (4).…”
mentioning
confidence: 99%
“…RFLP analysis revealed that ileal and hepatic isolates had identical banding patterns with AluI and HhaI restriction enzymes, but were distinct from the banding patterns of the colonic isolate. The RFLP patterns from the ileal and hepatic isolates were identical to the pattern of an isolate of 'Helicobacter macacae' (MIT 99-5504) obtained from the colon of a non-diarrheic rhesus monkey with chronic idiopathic colitis (Fox et al, 2001b). The RFLP pattern of the colonic isolate was identical to the pattern of an isolate of Helicobacter cinaedi (MIT 99-10781) obtained from the faeces of a rhesus monkey (J. G. Fox and others, unpublished results) (Fig.…”
Section: Pcr Was Performed On Individual Bacterial Isolates Usingmentioning
confidence: 64%
“…'H. macacae' is a novel species that has been isolated from rhesus monkeys with and without chronic idiopathic colitis (Fox et al, 2001b; J. G. Fox and others, unpublished results). 'H.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation